2019
DOI: 10.1108/jcs-05-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Care leavers’ views about transition: a literature review

Abstract: Purpose-Considerable attention has been given to the vulnerability of young people leaving care in the United Kingdom (UK) in their transition to adulthood. To date, however, there has been limited focus on the perceptions of care leavers about what factors enable and inhibit effective practice. Design/methodology/approach-This systematic literature review sought to elicit the views of UK care leavers in identifying barriers and facilitators to the process of transition to adulthood. Qualitative studies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Following Mendes and Moslehuddin (2006), we suggest the need to reconceptualise these young people's transitions as a move to ‘interdependence’ rather than ‘independence’. As Atkinson and Hyde (2019, p. 15) state: “Ultimately, UK care leavers wanted to be able to count (but not depend) on reliable others during a (gradual, not instantaneous) journey to independence.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Mendes and Moslehuddin (2006), we suggest the need to reconceptualise these young people's transitions as a move to ‘interdependence’ rather than ‘independence’. As Atkinson and Hyde (2019, p. 15) state: “Ultimately, UK care leavers wanted to be able to count (but not depend) on reliable others during a (gradual, not instantaneous) journey to independence.”…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified that care leavers often appreciate the support that engaged practitioners provide (Driscoll, 2013; Liabo et al., 2016). The ability of practitioners to recognise young people's strengths, manage transitions gradually and thereby provide space for them to make meaningful choices about their lives on leaving care is considered a core dimension of effective support (Atkinson & Hyde, 2019; Avery & Freundlich, 2009; Geenen & Powers, 2007; Leeson, 2007; Mendes & Moslehuddin, 2006). Such recognition can be seen both as an ethical commitment to young people's agency and as a way of supporting young people to make autonomous decisions on leaving care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, differences in somatosensory processing in those raised in foster care have not previously been reported. While the outcomes of growing up in foster care are more positive than institutionalized care, it is still a significant risk factor for poor mental-health and social isolation in later life (Stein, 2006;Gypen et al, 2017;Atkinson and Hyde, 2019), suggesting self-regulatory deficits are apparent in this group too. The blunted affective touch ratings reported in the present study provide further support for the theory that CTs are one mechanism by which early nurturing contact supports the development of an infant's physiological and emotional regulation (Craig, 2002;Björnsdotter et al, 2010;McGlone et al, 2017;Manzotti et al, 2019;Van Puyvelde et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, having been taken into care due to neglect and/or abuse this group, even when fostered, are likely to experience reduced nurturing contact in comparison to peers who have never been in care. Care leavers frequently experience social-exclusion in adulthood (Stein, 2006;Atkinson and Hyde, 2019), thus it seems plausible that a lack of nurturing touch during early critical or sensitive periods has significant consequences for later life social functioning. Initial evidence for this is provided by the significant negative relationship between childhood adversity and later life touch attitudes and experiences reported by Trotter et al (2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Young people leaving care are often disadvantaged in these transitions, which have been characterized as both 'accelerated and compressed' (Stein, 2012, p. 400). Care-experienced young people also need to negotiate inequalities in terms of education, employment and housing (Allnatt, 2019;Artamonovaa et al, 2020;Brady & Gilligan, 2019;Girling, 2019;Hyde & Atkinson, 2019).…”
Section: Introductionmentioning
confidence: 99%